A Novice Guide to Applications of Simulation in the Pediatric Emergency Department. Issue 6 (June 2020) - Waseem, Muhammad; Horsley, Elizabeth
Abstract : Abstract: Healthcare systems and health professions education have gone through radical changes in the past decades. These changes have made it imperative to explore innovative and alternative ways of teaching and training. Simulation-based education has emerged as an effective teaching strategy for both learners and practicing health professionals. Simulation is an educational technique that recreates real-life experiences. Learning occurs through participation in these simulation experiences followed by a period of guided debriefing and reflection. Pediatric emergency medicine, by its very nature, can benefit greatly from a well-designed and thoughtfully implemented simulation program. This review outlines situations where simulation may be used for maximum effectiveness in a pediatric emergency department and provides an overview of the basics of debriefing. A thorough description of each identified use of simulation is beyond the scope of this article. Abstract : Supplemental digital content is available in the text.